Bimbingan Teknis dan Penyerahan Mesin Pengaduk Adonan Dodol - Asmat Purba; Darwinto Darwinto; Agus Saleh; Yoddy Agung Nuhgraha (Apik Cahaya Ilmu, 2026)
This article discusses technical guidance and the handover of the dodol dough mixer machine. Until now, the dodol dough has been made manually and can take three to five hours per batch. Besides being less hygienic and efficient, dodol craftsmen cannot fulfill large orders, making them feel overwhelmed. The author uses literature review and interviews with dodol craftsmen in the Parongpong area of West Bandung. The aim of this study is to examine the extent of success brought by the dodol dough mixer machine in terms of production, cleanliness of dodol, and sales efficiency.